Peran Serviscape dalam Membangun Citra Rumah Sakit: Studi pada Unit Rawat Inap RSUD Lamaddukkelleng Sengkang - Andi Mikhrunnisai; Anugerah Yanuar Azis; A.Nur Azizah; Nur Fadilah Fitra (Lentera Pena Cendekia, 2026)
Servicescape, or the physical environment of a hospital, is an important factor that can shape patients' perceptions of the image of a healthcare institution. A clean, comfortable, well-organized environment supported by adequate facilities has the potential to enhance patients' trust in the hospital. This study aimed to determine the relationship between servicescape and hospital image in the Inpatient Unit of Lamaddukkelleng Regional General Hospital, Sengkang. A cross-sectional study design was employed using a proportional stratified random sampling technique. The study sample consisted of 100 respondents selected from a population of 14,204 patients. Data were collected using a structured questionnaire and analyzed through univariate and bivariate analyses using the Chi-Square test. The results showed that 68 respondents (68.0%) rated the servicescape as adequate, while 32 respondents (32.0%) rated it as inadequate. A total of 72 respondents (72.0%) had a positive perception of the hospital image, whereas 28 respondents (28.0%) had a negative perception. Among respondents who rated the servicescape as adequate, 54 (79.4%) had a positive perception of the hospital image, while only 18 respondents (56.3%) in the inadequate servicescape group had a positive perception. The Chi-Square test yielded a p-value of 0.030 (p < 0.05), indicating a significant relationship between servicescape and hospital image. It can be concluded that a well-maintained physical environment plays an important role in building a positive hospital image. Hospital management should continuously improve cleanliness, facility adequacy, room comfort, lighting, and environmental layout to strengthen patients' trust and positive perceptions of hospital services. Improving servicescape quality is expected to enhance patient experience, loyalty, and hospital competitiveness in healthcare delivery.